2018
DOI: 10.4236/eng.2018.107028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flow Structures Induced by Highly Rough Surface Using Particle Image Velocimetry, Proper Orthogonal Decomposition and Velocity Correlations

Abstract: High Reynolds number flow inside a channel of rectangular cross section is examined using Particle Image Velocimetry. One wall of the channel has been replaced with a surface of a roughness representative to that of real hydropower tunnels, i.e. a random terrain with roughness dimensions typically in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The temporally averaged velocity shows recirculation at the same position. These results, along with results presented by Andersson et al (2018), suggest vortex shedding occurring at the roughness element. When the flow is accelerated over the roughness element, the pressure will decline accordingly and fluid will congregate in the lowpressure zone downstream of the roughness element.…”
Section: Vortex Sheddingsupporting
confidence: 85%
See 1 more Smart Citation
“…The temporally averaged velocity shows recirculation at the same position. These results, along with results presented by Andersson et al (2018), suggest vortex shedding occurring at the roughness element. When the flow is accelerated over the roughness element, the pressure will decline accordingly and fluid will congregate in the lowpressure zone downstream of the roughness element.…”
Section: Vortex Sheddingsupporting
confidence: 85%
“…Hence, second quadrant events are dominant in this area, associated with strong turbulent production, ejection of fluid away from the wall and rapid oscillations in the flow (Kim et al, 1987). Similarly, quadrant analysis at ū max showed an overwhelming dominance of Q2 events according to Bennet and Best (1995) and Andersson et al (2018). The peaks in the flatness are caused by surges in both velocity components, connected to the vortex shedding occurring at the roughness element.…”
Section: Higher-order Statisticsmentioning
confidence: 87%
“…The extremes range from 10 to 1500 depending on the position of the tunnel wall. Earlier studies [7,8] have shown that the majority of the frictional losses come from the large scale roughness, hence, numerical wall-functions will have a small effect on the resulting flow. Numerically, the k-ε model is relatively cheap compared to e.g., LES and it is known to capture the main flow behaviour for similar applications [8].…”
Section: Discretization and Simulation Setupmentioning
confidence: 99%
“…It has been shown that, indeed, the roughness may have a dominant effect on the flow in the tunnel i.e., the flow parameters are highly dependent on where you measure inside of the tunnel [7]. In this work, the relation between the static pressure and the cross-section of the tunnel is evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been widely employed in the optimization design of airfoil and turbomachinery [4][5][6][7], flow field efficiency and stability of eigenvalue solution and having better applicability in data prediction. Therefore, it has been widely employed in the optimization design of airfoil and turbomachinery [4][5][6][7], flow field analysis [8][9][10][11], and data mining [12]. The third author [13][14][15] of this paper applied the POD method to the inverse problem of a centrifugal pump impeller, with a modal analysis of the flow field and a reconstruction of the gas-liquid two-phase flow field of a liquid ring pump, which extends the ideas and methods of flow characteristic analysis and optimization design of a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%